Agri-Food Supply and Retail Food Prices during the Russia–Ukraine Conflict’s Early Stage: Implications for Food Security - Mariusz Hamulczuk; Karolina Pawlak; Joanna Stefańczyk; Jarosław Gołębiewski (Agriculture, 2023)
The Russian–Ukrainian conflict has led to the disruption of global supply chains, thus posing a threat to food security. The study aimed to assess the short-term impact of the conflict on food supply and global retail food prices resulting from the disruption of agri-food exports from Ukraine after the war outbreak. To assess the impact of the conflict on retail prices worldwide, the actual food price level during the conflict period was compared with the counterfactual values obtained from the forecasting models. The research points to a significant decline in Ukraine’s commodity exports at the beginning of the conflict leading to a supply gap for cereals in particular, affecting global access to staple foods. As a result, global food commodity prices rose sharply, however, the upsurge was short-lived, and as early as July 2022 price indices returned to their pre-war levels. On the other hand, in most regions worldwide the gradual and persistent increase in retail food prices was observed after the war outbreak. The study also found strong regional differentiation in the response of retail food prices to the conflict due to various specific factors that exacerbated or mitigated the impact of the war.